Shaping identity in medieval French literature the other within - Tudor, Adrian; Burr, Kristin L. (University Press of Florida, 2019)
This collection of essays argues that literary identity can be created and re-created, adopted, refused, imposed, and self-imposed, and that one may exist within a group while remaining foreign to it. Contributors examine this theme through a wide range of lenses--from marginal characters to gender to questions of voice and naming--in works that span genres and historical periods